Peningkatan Pengetahuan tentang Jajanan Sehat Pada Siswa Madrasah Ibtidaiyah Nurussalam Mantingan Ngawi - Amilia Yuni Damayanti; Lulu’ Luthfiya; Kartika Pibriyanti; Hasya Syilmi Esyafir; Mardhatillah Mardhatillah; Rosa Kamila (Janaka, Jurnal Pengabdian Masyarakat, 2022)
Healthy food is an important thing to keep body health and growth of children. Snack foods play an important role in the supply of energy and other nutrients for school-age children. The age of 6-12 years is a period of transition from pre-school to elementary school. Lack of knowledge is one of the reasons children like to eat unhealthy snacks. Education for children needs to be carried out so that children have the knowledge to differentiate between healthy snacks and unhealthy snacks. The objective from this activity is increasing the knowledge of children of elementary school regarding healthy snacks. The method used is counseling about healthy snacks to school children. The results showed that after counseling, the level of knowledge of respondents about healthy snacks increased, as many as 40% of respondents got a score of 100, 31% got a score of 80, 16% got a score of 60, 11% got a score of 40 and 2% got a score of 20.